2011
DOI: 10.1002/chem.201002462
|View full text |Cite
|
Sign up to set email alerts
|

Poly(triazine imide) with Intercalation of Lithium and Chloride Ions [(C3N3)2(NHxLi1−x)3⋅LiCl]: A Crystalline 2D Carbon Nitride Network

Abstract: Poly(triazine imide) with intercalation of lithium and chloride ions (PTI/Li(+)Cl(-)) was synthesized by temperature-induced condensation of dicyandiamide in a eutectic mixture of lithium chloride and potassium chloride as solvent. By using this ionothermal approach the well-known problem of insufficient crystallinity of carbon nitride (CN) condensation products could be overcome. The structural characterization of PTI/Li(+)Cl(-) resulted from a complementary approach using spectroscopic methods as well as dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
302
0
9

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 313 publications
(336 citation statements)
references
References 80 publications
(110 reference statements)
20
302
0
9
Order By: Relevance
“…These spectra more closely resemble the 15 N CP-MAS measured for the Pharaoh's serpent material than those of PTI·LiCl, [41] PTI·LiBr, [42] or PTI·HBr. [37] We note that Lotsch et al [11] prepared a 15 N-enriched sample of Liebig's melon that allowed them to observe of a small signal at approximately -225 ppm (δ =156 ppm relative to MeNO 2 ) that could be unambiguously assigned to the central N c atom of the heptazine structural unit.…”
Section: Articlesupporting
confidence: 60%
“…These spectra more closely resemble the 15 N CP-MAS measured for the Pharaoh's serpent material than those of PTI·LiCl, [41] PTI·LiBr, [42] or PTI·HBr. [37] We note that Lotsch et al [11] prepared a 15 N-enriched sample of Liebig's melon that allowed them to observe of a small signal at approximately -225 ppm (δ =156 ppm relative to MeNO 2 ) that could be unambiguously assigned to the central N c atom of the heptazine structural unit.…”
Section: Articlesupporting
confidence: 60%
“…1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 4 DFT calculations were used to describe the copolymerization effects on the structure and optical properties. The CN was modeled by the incompletely polymerized PTI-0 structure proposed by Lotsch and coworkers, 57 from which LiCl was removed, thus leading to the composition g-C 6 N 9 H 3 . Refining the P6 3 cm structure proposed in the literature yielded a local minimum with P6 3 /mcm symmetry.…”
Section: Resultsmentioning
confidence: 99%
“…Scanning electron microscopy (SEM) examination (Figure 2b) indicated that gCNM exhibits a latticework of interlocking planar microstructures with individual layer thicknesses on the order of 2-3 nm that give rise to porous aggregates with pore sizes on the order of a few nm. This material is not very highly condensed, and its structure could be close to that of Liebig's melon or melem that are built from "ribbons" of PH polymeric units (56,60,61), but with the possibility that PTI units may also be contained within the structure derived from the melamine precursor. The aggregates are fused together to give rise to much larger pores (1-2 µm) within the resulting solid.…”
Section: Resultsmentioning
confidence: 99%
“…The aggregates are fused together to give rise to much larger pores (1-2 µm) within the resulting solid. BET measurements revealed a surface area of 28 m ) was prepared using an ionothermal route (56,57). This method allowed us to obtain a highly crystalline carbon nitride using relatively mild conditions.…”
Section: Resultsmentioning
confidence: 99%